3x-5(x-5)=7+2x+4

Simple and best practice solution for 3x-5(x-5)=7+2x+4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-5(x-5)=7+2x+4 equation:


Simplifying
3x + -5(x + -5) = 7 + 2x + 4

Reorder the terms:
3x + -5(-5 + x) = 7 + 2x + 4
3x + (-5 * -5 + x * -5) = 7 + 2x + 4
3x + (25 + -5x) = 7 + 2x + 4

Reorder the terms:
25 + 3x + -5x = 7 + 2x + 4

Combine like terms: 3x + -5x = -2x
25 + -2x = 7 + 2x + 4

Reorder the terms:
25 + -2x = 7 + 4 + 2x

Combine like terms: 7 + 4 = 11
25 + -2x = 11 + 2x

Solving
25 + -2x = 11 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
25 + -2x + -2x = 11 + 2x + -2x

Combine like terms: -2x + -2x = -4x
25 + -4x = 11 + 2x + -2x

Combine like terms: 2x + -2x = 0
25 + -4x = 11 + 0
25 + -4x = 11

Add '-25' to each side of the equation.
25 + -25 + -4x = 11 + -25

Combine like terms: 25 + -25 = 0
0 + -4x = 11 + -25
-4x = 11 + -25

Combine like terms: 11 + -25 = -14
-4x = -14

Divide each side by '-4'.
x = 3.5

Simplifying
x = 3.5

See similar equations:

| 6x-3=-11 | | m=10-x | | 8.1+1.8h=-7.2 | | (M-7)(m-3)=0 | | 45-61=4x-2x | | 1.5x+0.5=12 | | 3x-4x=-22 | | bx-ay+2z=-19 | | 72y+4.7=62.3 | | 6x^2-3=x^3-169 | | 4a+5b+c=6 | | -x-3(2)=-11 | | 9r^2+2r-24=0 | | 30x=540 | | 5-4k=12x+7 | | x^2+7x+20=3x+17 | | -9y+3x=-9 | | 95m-2=80a+3 | | 6=10(k+.6) | | 2x+22+122=14x | | m/(-3)=-5-18 | | 6x-5+8x-2x-3=9w-24 | | 0.40x+0.25(140)=0.20(113) | | 5t-2=3t-8+8t | | 3x(5)+3=18 | | m^2+7m+5=0 | | 10t-4t=-11 | | 2x+19=8x-41 | | 12p+3q-5p+8q= | | 3a-b+c=10 | | 16x+8=32x+16 | | 1.055=x^15 |

Equations solver categories